Comparative effectiveness of monomolecular surface film on Aedes aegypti (L.) and Anopheles minimus (Theobald) (Diptera: Culicidae) - Sukkanon, Chutipong; Yaicharoen, Rapeeporn; Ngrenngarmlert, Warunee (Agriculture and Natural Resources, 2016)
Silicone-based surfactants have become of interest for mosquito control in Thailand. When this non-ionic surfactant is applied in mosquito habitats, a monomolecular film (MMF) forms on the water surface and disrupts the ability of larvae and pupae to breathe. In this study, a laboratory bioassay was conducted to determine the mosquito control potential of MMF against Aedes aegypti (L.) and Anopheles minimus (Theobald), and to compare its efficacy with other larvicides consisting of temephos (an organophosphate), Bacillus thuringiensis israelensis (Bti) and pyriproxyfen (an insect growth regulator). It was determined that the percentage mortality of Ae. aegypti and An. minimus treated with MMF at a recommended dosage of 1 mL/m2 was significantly greater in pupae (99.2% and 100%, respectively) than old stage larvae (L3-L4, age 46 d; 70.8% and 97.5%, respectively) and young stage larvae (L1-L2, age 1-2 d; 8.3% and 58.0%, respectively). Small larvae and prolonged stage transformations indicated MMF growth inhibition activity. MMF also displayed oviposition deterrence behavior and caused female mosquitoes to drown during egg laying. In comparison, temephos and Bti were highly effective in larval control while pyriproxyfen and MMF provided excellent control effects against the pupal stage. Based on the results, MMF showed promise as an alternative larvicide for mosquito control in Thailand. Further studies on the environmental effects of MMF are needed.